GE_GERICHTE PM/1392/2024 vom 29. August 2025 - GE Cour de justice (2025)
EXÉCUTION ANTICIPÉE DES PEINES ET DES MESURES;LIBÉRATION CONDITIONNELLE;INTERNEMENT(DROIT PÉNAL);MESURE THÉRAPEUTIQUE INSTITUTIONNELLE | CP.59; CP.64; CP.64.al1.let a et b; CP.64.al2